Ashwamedha Yagya in Puran - Manisha Bhardwaj (Dr. Chinmay Pandya, 2024)
The Ashwamedha yagya is one of the most important ritualistic practices in Indian culture and society. It was performed to uplift human consciousness and refine mass consciousness. The Puranas serve as excellent sources for understanding the history of Indian society, containing information about lineages, dynasties, and their actions. The present study aims to provide an overview of instances where accounts of the Ashwamedha yagya were performed in history. Instances of Ashwamedh yagya are ample in the Puranas. Ashwamedha Yagya in the Chandravanshi (Lunar Dynasty) (Mahabharat era), Ikshvaku Dynasty (Ramayan era), Ashwamedha Yagya in Other Great Dynasties including beyond Ramayan era, and Ashwamedha Yagya by the Great Sages are noted in the present perspective review. Furthermore, stories of the performance of the Ashwamedha Yagya abound in the Puranas, indicating that these rituals were among the most sacred and highly revered events in ancient Indian culture.